2009
DOI: 10.1063/1.3277141
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal heterogeneity in supercooled glycerol: Evidence from wide field single molecule imaging

Abstract: We quantify spatial and temporal heterogeneity in supercooled glycerol at T=T(g)+14 K employing a widefield detection scheme and using rubrene as the probe molecule. We describe how microscopy configuration affects measured intensity, linear dichroism, and the resulting autocorrelation function. Rotational relaxation times tau(c) of 241 probe molecules are measured, and we find spatial heterogeneity over almost three orders of magnitude present at this temperature. An approach for detecting temporally heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
87
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 50 publications
(92 reference statements)
6
87
1
4
Order By: Relevance
“…Similarly, it is shown that the median τ c is underestimated for short trajectories. These results are consistent with earlier studies on the effects of time-limited trajectories on homogeneous dynamics6,13. For heterogeneous systems with FWHM input of < 0.6, the measured FWHM of the shortest trajectory measurements is overestimated, as in the homogeneous case.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, it is shown that the median τ c is underestimated for short trajectories. These results are consistent with earlier studies on the effects of time-limited trajectories on homogeneous dynamics6,13. For heterogeneous systems with FWHM input of < 0.6, the measured FWHM of the shortest trajectory measurements is overestimated, as in the homogeneous case.…”
supporting
confidence: 92%
“…Fluorescence from probe molecules is used to construct SM linear dichroism (LD) trajectories and the ACF of each LD trajectory is fit to either single or stretched exponential decays. While the magnitude of the deviation of β from 1.0 of an ACF measured in an ensemble experiment is generally interpreted as correlating with the degree of heterogeneity in the system, for SM LD ACFs this is not generally assumed1,6,13. This is because typical SM trajectories are 10-200 τ c , short enough such that trajectories associated with homogeneous dynamics may be best fit by stretched exponential decays with β values significantly different than 1.013.…”
mentioning
confidence: 99%
“…This point was first addressed in pioneering works with four-dimensional NMR [9] and direct probing of fluctuations at the nanoscopic scale using atomic force microscopy techniques in polymeric glasses [10]. Direct visualizations of molecular trajectories are not yet possible, but recent, very elegant experimental approaches using single-molecule spectroscopy are getting close to it [11,12]. Direct visualization is possible for different types of glasses, such as colloidal [13] and granular [14,15] assemblies.…”
Section: What Is Dynamic Heterogeneity?mentioning
confidence: 99%
“…Fluorescence microscopy of single molecules confirms the presence of large variations in the local viscosities. [7][8][9][10][11] Zondervan et al observed that these variations can be surprisingly long-lived, even at temperatures well above the glass transition temperature (T g ). 9 This may indicate the existence of a nearly static solid-like network at temperatures above T g , which was also revealed by rheological measurements.…”
Section: Introductionmentioning
confidence: 99%